Bagaimana Utang Mendorong Terjadinya Krisis? Solusi dari Sistem Keuangan Islam - Muhammad Arfan Harahap; Yochi Elanda; M. Sabri A. Majid; Marliyah Marliyah; Rita Handayani (Reslaj : Religion Education Social Laa Roiba Journal, 2022)
Interest-based debt is prohibited in Islam because of its exploitative nature. The main purpose of implementing Islamic sharia in financial activities is to eliminate injustice and inequalities in financial transactions. The main characteristic of Islamic finance is the prohibition of charging interest, also known as usury. The findings in this study that debt that was continuously extended during the crisis did not have the effect of restoring the economy to normal conditions, instead providing an impetus for a continuous crisis. Interest-based debt is a dangerous weapon to exploit and extort poor people who need venture capital. Furthermore, the high interest in using interest-based debt is exploited by the surplus capital to increase their wealth. Interest-based debt with high costs weakens the economy, although from a capital turnover perspective it looks bigger. The solution of the Islamic financial system with an interest-free loan scheme (Qardhul Hasan) is an alternative that has been proven to provide an incentive to increase welfare. Qardhul Hasan with a low cost becomes effective in increasing output, absorbing employment, and maintaining a low inflation rate without creating negative side effects in the economy. Keywords: debt, interest, crisis, qardhul hasan